Maintained superiority of chronotherapeutics vs. exercise in a 20‐week randomized follow‐up trial in major depression. (17th February 2015) - Martiny, K.; Refsgaard, E.; Lund, V.; Lunde, M.; Thougaard, B.; Lindberg, L.; Bech, P.
<x xml:space="preserve">Abstract</x> Objective To investigate the long‐term antidepressant effect of a chronotherapeutic intervention. Method In this randomized controlled trial 75 patients with major depression were allocated to fixed duloxetine and either a chronotherapeutic intervention (wake group) with three initial wake therapies, daily bright light therapy, and sleep time stabilization or to a group using daily exercise. Patients were followed 29 weeks. We report the last 20 weeks, a follow‐up phase, where medication could be altered. Patients were assessed every 4 weeks. Remission rates were primary outcome. Results Patients in the wake group had a statistically significant higher remission rate of 61.9% vs. 37.9% in the exercise group at week 29 (OR = 2.6, CL = 1.3–5.6, P = 0.01). This indicated continued improvement compared with the 9 weeks of treatment response (44.8% vs. 23.4%) with maintenance of the large difference between groups. HAM‐D17 endpoint scores were statistically lower in the wake group with endpoint scores of 7.5 (SE = 0.9) vs. 10.1 (SE = 0.9) in the exercise group (difference 2.7, CL = 0.5–4.8, P = 0.02). Conclusion In this clinical study patients continued to improve in the follow‐up phase and obtained very high remission rates. This is the first study to show adjunct short‐term wake therapy and long‐term bright light therapy as an effective and feasible method to attain and maintain remission.